Pengembangan Modul IPA Materi Penanganan Sampah Berbasis 3R (Reduce, Reuse, dan Recycle) Menuju Zero Waste: Development of Science Module for 3R Based Waste Management Materials (Reduce, Reuse, and Recycle) Towards Zero Waste - Neni Marsolina; Evita Anggereini; Nazarudin (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
Modules are the smallest program units that can be studied by individual students (self instructional). The purpose of this study is to provide an overview of how module development is, as well as the feasibility and effectiveness of modules being developed. The research method used is Research and Development. In this study contains how to develop modules through the validation stage by material experts and media experts. Source of data used in this study were students and teachers of SMK N 1 Kota Jambi. The results showed that the module developed was worthy of material experts with a value of 78.8% and was very feasible by media experts 90.4%, after being revised, it was tested on teachers and students. The teacher response test scores 94% criteria very well, the small group test scores 87.8% and the large group test scores 88%. The effectiveness of the module on students' environmental awareness values ​​for the experimental class 89.8%. Based on the results of the study, it can be concluded that the science learning module on 3R-based waste handling materials (Reduce, Reuse, Recycle) gets a proper assessment from the experts, very good and effective towards the environmental concern of students.